The Black Panther Party and Emancipatory Adult Education - Geleana D Alston Ph.D. (Adult Education Research Conference, 2017)
This session will illuminate the emancipatory adult educational efforts of the Black Panther Party Community Programs from 1966-1982.
Keywords: History of Adult Education; Black Panther Party; African Americans